Evaluation methods for pretransplant oncologic markers and their prognostic impacts in patient undergoing living donor liver transplantation for hepatocellular carcinoma. (21st February 2014) - Shindoh, Junichi; Sugawara, Yasuhiko; Nagata, Rihito; Kaneko, Junichi; Tamura, Sumihito; Aoki, Taku; Sakamoto, Yoshihiro; Hasegawa, Kiyoshi; Tanaka, Tomohiro; Kokudo, Norihiro
Summary Tumor markers [alpha‐fetoprotein (AFP) or des‐gamma‐carboxyprothrombin (DCP)] and neutrophil/lymphocyte ratio (NLR) reportedly correlate with long‐term outcomes for hepatocellular carcinoma (HCC). However, no standardized method has been established for evaluating the pretransplant data. One hundred and twenty‐four patients who underwent living donor liver transplantation (LDLT) were retrospectively reviewed. The best predictive parameters for tumor recurrence were maximum values for AFP or DCP and 90‐day mean values for NLR, respectively, and multivariate analysis confirmed these values were correlated with tumor recurrence. However, receiver operating characteristic analysis revealed that discriminative powers were sufficient only in maximum AFP [area under the curve (AUC) 0.88, P < 0.001] and maximum DCP (AUC 0.76, P < 0.001), while mean NLR was less predictive (AUC 0.62, P = 0.20). When incorporating AFP and DCP to the Tokyo criteria (≤5 tumors with each tumor ≤5 cm), the presence of at least two of the following factors: (i) beyond the Tokyo criteria, (ii) AFP>250 ng/ml, and (iii) DCP > 450 mAu/ml (>450 ng/ml), was correlated with a worse 5‐year disease‐free survival rate (20.0% vs. 96.8%, P < 0.001) and 5‐year overall survival rate (20.0% vs. 84.0%, P < 0.001). The prognosis of patients undergoing LDLT for HCC strongly relies on maximum AFP or DCP values before transplantation, while the prognostic impact of NLR is limited.